2015
DOI: 10.1111/nan.12180
|View full text |Cite
|
Sign up to set email alerts
|

Mice with experimental antiphospholipid syndrome display hippocampal dysfunction and a reduction of dendritic complexity in hippocampal CA1 neurones

Abstract: Reduction of hippocampal dendritic complexity may represent the structural basis for the behavioural and cognitive abnormalities of eAPS mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 45 publications
0
15
0
2
Order By: Relevance
“…There is evidence in paradigms that test the effects of different molecules, like hormones or drugs of abuse, or learning and memory experiments, that altered spine density plays an important mechanistic role in the studied behaviors [5254]. Reports in preclinical experiments demonstrate that acquired disorders of the nervous system, including autoimmune disorders, can alter neuronal structural integrity, particularly dendrite arbors [55, 56]. There is also precedent for alterations in spine density and dendritic arbors in various psychiatric and genetic disorders [50, 57, 58].…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence in paradigms that test the effects of different molecules, like hormones or drugs of abuse, or learning and memory experiments, that altered spine density plays an important mechanistic role in the studied behaviors [5254]. Reports in preclinical experiments demonstrate that acquired disorders of the nervous system, including autoimmune disorders, can alter neuronal structural integrity, particularly dendrite arbors [55, 56]. There is also precedent for alterations in spine density and dendritic arbors in various psychiatric and genetic disorders [50, 57, 58].…”
Section: Resultsmentioning
confidence: 99%
“…It is also noteworthy that experimental and clinical work has demonstrated the association of abnormal dendritic arborization patterns, together with altered dendritic spine density, in various psychiatric and genetic disorders (63)(64)(65). Other reports have shown that acquired disorders of the nervous system, including autoimmune disorders, can alter neuronal structural integrity (66)(67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…Since SLE patients carrying elevated titers of DNRAbs exhibited impaired spatial memory compared to HC subjects, the mouse model appears to be a valid model for NPSLE. Changes in dendritic complexity in hippocampal neurons have been reported in a model of anti-phospholipid syndrome, although the mechanism for neuronal destruction in unknown ( Frauenknecht et al, 2014 ). There are numerous brain-reactive antibodies in SLE ( Yaniv et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%